TANGGAPAN MAHASISWA CALON GURU SD TERHADAP PENERAPAN ASESMEN E-PORTFOLIO - , SURYANTI (Pendidikan Dasar, 2009)
Abstract: Nowadays information and communication technology has been used in education, including in the assessment. The purpose of this study was to discover and explain the fundamental lessons learned from the beginning stages of e-Portfolio implementation as part of assessments on Science Education for prospective elementary school teachers. Subject of this research were students of S1 PGSD, amounted to 40 people. e-Portfolio assessment system utilized the site as a popular blog where students can upload his artifacts and to watch and assess peers’ artifacts. At the end of the semester students got questionnaire about four learning outcomes through the e-Portfolio: increasing of information and communication technology skills, self-confidence, self-reflection, and willingness to grow. After the implementation of e-Portfolio assessment during one semester, the students stated more confidence to take advantage and improve the skills of information technology. This study also showed, through e-Portfolio assessment, almost all students wished to continue to grow in the form of showing his artifacts. However, students did not make the self-reflection yet, which is one of the key ability to develop himself.